How to Promote Bedside Placement of the Postpyloric Feeding Tube: A Network Meta-Analysis of Randomized Controlled Trials. (July 2015) - Tiancha, Huang; Jiyong, Jing; Min, Yan
Background: The optimal method of achieving fast, safe, and accurate postpyloric tube placement at the bedside remains controversial. This study investigated whether facilitating techniques of bedside placement would improve the rate of successful placement of postpyloric tubes when compared with the standard technique and whether strategies should be confined to adult or pediatric patients. Methods: We searched electronic databases for eligible literatures that compared different methods of postpyloric tube placement, evaluating the successful rate of postpyloric tube placement. Two reviewers reviewed the quality of the studies and performed data extraction independently. Pairwise and network meta-analyses were performed to integrate the efficacy. Results: Fourteen clinical trials involving 753 patients were included. Pairwise meta-analyses demonstrated that prokinetic agents (odds ratio [OR], 2.263; 95% confidence interval [CI]: 1.140–4.490; P = .02) were associated with a higher success rate as compared with the standard technique, and gastric air insufflation was associated with a higher success rate as compared with prokinetic agents (OR, 3.462; 95% CI, 1.63–7.346; P = .001) in adult patients. In network analyses, prokinetic agents and gastric air insufflation were also consistently associated with a higher success rate in adult patients. Trend analyses of rank probabilities revealed gastric air insufflation had the cumulative probability of being the most efficacious strategy (78%), especially in adult patients (88%). Conclusions: Gastric air insufflation seems to be clinically better for promoting bedside placement of postpyloric feeding tubes in adults. Clinicians should no longer use prokinetic agents in pediatric patients or patients without impaired motility.